IMPLEMENTASI FIREBASE CLOUD MESSAGING PADA APLIKASI BROADCAST INFORMASI PERKULIAHAN UNTUK MEMPERCEPAT PENDISTRIBUSIAN INFORMASI DI STMIK KHARISMA MAKASSAR - Indrawan Liwanto; Hamdan Arfandy; Abdul Munir S. (STMIK KHARISMA Makassar, 2019)
The purpose of this research is to implement Firebase Cloud Messaging on Broadcast Information Lecture Application to Speed Up Information Distribution at STMIK Kharisma Makassar. In developing this application, the author uses Android Studio. The database uses the Cloud Firestore and Firebase Cloud Messaging service in terms of notifications in real time. In measuring the application functionality, the author uses the black box method. To measure the speed of information distribution, the authors conducted a speed test. Whereas to measure the quality of the application the author uses a questionnaire method that is distributed to several academics of STMIK Kharisma Makassar. The results showed: 1) the development stage of lecture information distribution application includes, data collection, planning, development, and application evaluation, 2) the development of lecture information distribution application declared appropriate for use based on, a) the results of functionality with the black box method went well, b) the results of information distribution speed testing are 2,006 seconds faster than the previous method, and c) the results of responses of respondents on the questionnaire with an average score of 92% or the category